PHARMACOLOGICAL TREATMENT STRATEGIES FOR ADHD: A SYSTEMATIC REVIEW - Paweł Grzesikowski; Paulina Klich; Kinga Bekier; Jakub Kubiak; Jan Górski; Hanna Nowicka; Dominika Liszka; Maria Joks; Emmanuelle Ordon; Kamila Ostromecka (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Attention deficit hyperactivity disorder (ADHD) is one of the most commonly diagnosed neurodevelopmental disorders in children and adolescents. Various treatment methods are available for this condition, including pharmacological and non-pharmacological strategies. Pharmacotherapy is currently the most effective method of reducing the core symptoms of ADHD. The most commonly used medications include psychostimulants such as methylphenidate and amphetamines. Comparing the efficacy and safety of available medications is particularly important in order to select the appropriate treatment for individual.Aim of the study: The aim of our study is to review the available literature on the pharmacological treatment of attention deficit hyperactivity disorder and to summarize current knowledge. We presented the mechanisms of action, clinical efficacy, and safety profile of individual drugs used in the pharmacotherapy of ADHD.Methods and materials: We reviewed the literature available in the PubMed database using the following keywords: “ADHD treatment”; “Attention Deficit Hyperactivity Disorder treatment”; “Stimulants”; “Non-stimulants”; “Methylphenidate”; “Atomoxetine”; “ADHD”; “Bupropion”; ‘Modafinil’; “α-agonists”; “Lisdexamphetamine (LDX)”; “Mixed Amphetamine Salts”, “Clonidine”; “Viloxazine”; “Centanafadine”Conclusion: Pharmacotherapy is the most effective method of reducing the core symptoms of ADHD. Psychostimulants are currently considered the most effective and most commonly used drugs for the treatment of attention deficit hyperactivity disorder. In cases of intolerance or contraindications to their use, non-stimulant medications are an alternative. New medications such as viloxazine and centanafadine also offer promising alternatives. Individualization of pharmacological treatment is crucial to achieve optimal results.